2012
DOI: 10.1111/j.1460-2466.2012.01649.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Mood Management as Need Satisfaction: The Effects of Intrinsic Needs on Selective Exposure and Mood Repair

Abstract: This study attempted to (a) extend traditional mood management theory research by investigating the influence of the intrinsic needs for competence and autonomy on selective exposure to video games and (b) test the influence of satisfying these needs on resultant mood repair. An experiment varied satisfaction of competence and autonomy needs using false feedback. Subjects then selected media that varied in level of user demand. Measures of need satisfaction were taken before and after media selection. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 31 publications
9
112
0
Order By: Relevance
“…Another study found that selective exposure to valenced online news was based on mood adjustment needs (Knobloch-Westerwick & Alter, 2006). One study demonstrated that mood management affects choice of video game difficulty settings (Reinecke et al, 2012). Clearly, with the development of new forms of web content, including social media, new opportunities have arisen for mood management.…”
Section: Mood Management Onlinementioning
confidence: 97%
See 1 more Smart Citation
“…Another study found that selective exposure to valenced online news was based on mood adjustment needs (Knobloch-Westerwick & Alter, 2006). One study demonstrated that mood management affects choice of video game difficulty settings (Reinecke et al, 2012). Clearly, with the development of new forms of web content, including social media, new opportunities have arisen for mood management.…”
Section: Mood Management Onlinementioning
confidence: 97%
“…Mood was induced through a false-feedback protocol commonly used in mood management research (Biswas, Riffe, & Zillmann, 1994;Knobloch & Zillmann, 2002;Knobloch-Westerwick & Alter, 2006;Reinecke et al, 2012;Zillmann, Hezel, & Medoff, 1980), which was programmed in Authorware by the second author. Participants were asked to perform a ''facial expression recognition task'' in which 20 images of ambiguous facial expressions were categorized by discrete emotions.…”
Section: Mood Inductionmentioning
confidence: 99%
“…However, work by Reinecke et al (2012) specifically examined choice of video game difficulty level: participants first had a chance to try a flight simulator game in three different difficulty levels and then went through a mood induction procedure (the same as used by Knobloch & Zillmann, 2002, and slightly varied by KnoblochWesterwick & Alter, 2006). In the negative affect condition, participants chose a more demanding setting when they were asked to play the flight simulator game again compared to the positive affect condition.…”
Section: Mood Managementmentioning
confidence: 99%
“…Reinecke et al (2012) found that mood repair indeed occurred through video gaming for which users could select the difficulty level.…”
Section: Consequences Of Selective Exposure In the Context Of New Commentioning
confidence: 99%
“…Moreover, the model suggests that video games may have the ability to meet three critical needs: autonomy, relatedness, and competence (Ferguson & Olson, 2013;Reinecke et al, 2012;Tamborini, Bowman, Eden, Grizzard, & Organ, 2010). The autonomy need proposes that players can feel as though they have some form of power or control that they may not be able to experience in the real world.…”
Section: Findings On Game Play Motivations Of Playersmentioning
confidence: 99%